Crack propagation rate of hydrogen-induced cracking in high sulfur-containing pipelines. (May 2021) - Dong, Shaohua; Zhang, Laibin; Zhang, Hewei
Highlights: The mechanism involved in hydrogen induced cracking was revealed. Establish the expression for the fractal crack propagation and straight crack propagation rate. The results show a lower fractal propagation rate compared to that of the welding material. Abstract: Hydrogen-Induced Cracking (HIC) is one of the main failure models of pipeline steels that are utilized to gather pipeline networks and long-distance pipeline networks within high sulfur-containing gas fields. This phenomenon is mainly caused by the combined effects of hydrogen and stress after the hydrogen atoms or ions in the transmission medium entering into the steel. This can produce a stress corrosion effect on the materials and thus lead to a decrease of fracture ductile or degradation of other properties. In this paper, a micro-fracture shear band fractal model of HIC has been proposed and the mechanism of HIC has been studied. Both the shape of the fracture process zone and the step length of hydrogen-induced crack propagation were integrated, thus building expressions that describe the fractal rate of each step of HIC. Based on this, the fractal crack propagation rates of HIC in pipelines 16 Mn and 20 steel were calculated under certain working conditions and H2 S concentrations. Our study adds valuable insight into the life prediction of pipeline failure under the HIC environment.